Konstitusi dan Implikasi UUD 1945 dalam Era Modern - Aqbil Daffa Siahaan; Sasmi Nelwati (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Constitution comes from the English Contitution, or the Dutch Contitute, which means basic law. The meaning of constitution in constitutional practice can generally mean that first it is broader than basic law because the meaning of basic law only includes written constitutions in cases still there is an unwritten constitution that is not included in the constitution. Both have the same meaning as the constitution because they only contain written rules. The role of the constitution and the 1945 Constitution in the context of the modern era. The constitution is a document that regulates the structure of government, individual rights, and the relationship between the government and the people. The 1945 Constitution as the Indonesian constitution has a long history and has undergone various changes in adapting to current developments. This article will also discuss the implications of the 1945 Constitution in facing modern challenges such as technology, human rights and globalization. Constitutional research methodology involves a multidisciplinary approach that combines legal, historical, and sociopolitical perspectives. This approach allows for a comprehensive understanding of constitutional principles and their implications in modern times. The study of constitutional law often involves analysis of legal texts, historical context, legal interpretation, and social impact to gain a holistic view of constitutional provisions and their application.